1
$\begingroup$

I have a problem that suppose $μ,v$ are two linear maps belongs to $Hom(K^n,K^m)$

And $M_μ, M_v$ are the matrices of these two linear maps and $M_{(μ+v)}$ is the matrix of the sum of two linear maps.

So, how to prove that $M_μ + M_v = M{_(μ+v)}$?

I don't know how express the matrix of the sum of two linear maps so I get stuck. Can anyone help me out? Thank you!

Picture below is the definition of the matrix of a linear map, hope it can help

$\endgroup$
2
$\begingroup$

Start by showing the following:

  • For any transformation $T$ as in your definition and $x = [x_1\;x_2\;\cdots\;x_n] \in K^n$, $[T]_\beta^\gamma x = T\left[\sum_i x_iv_i \right]$

  • For any two matrices $M_1,M_2 \in K^{m \times n}$ are the same if and only if $M_1x = M_2x$ for every vector $x \in K^n$.

From there it suffices to note that for any $x = [x_1\;x_2\;\cdots\;x_n]$, we have $$ M_{(\mu + \nu)} x = (\mu + \nu)\left[\sum x_i v_i \right] = \mu\left[\sum x_i v_i \right] + \nu\left[\sum x_i v_i \right] = M_\mu x + M_\nu x = (M_\mu + M_\nu)x $$ Since this is true for all $x$, it must be that $M_{(\mu + \nu)} = M_\mu + M_\nu$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.